KRIMINOLOGI TERHADAP TINDAK PIDANA PENIPUAN YANG DILAKUKAN SECARA BERSAMA-SAMA DALAM PUTUSAN NOMOR: 6/Pid.B/2021/PN SLK - Rangga Prayitno; Rifka Zuwanda; Firdaus; Rus Yandi; Basrial Zuhri (Ekasakti Jurnal Penelitian dan Pengabdian, 2024)
Starting from the bad economy in Indonesia, many criminal acts of fraud began to occur which made people anxious due to the negative impact of the Covid-19 outbreak. The crime of fraud has spread to the Solok Regency area by taking advantage of people's negligence towards technology, especially electronic social media, making it very easy for perpetrators of fraud to carry out their plans by doing it together. The specifications of this research are analytical descriptive. The approach used is a normative juridical approach. The normative juridical approach is an approach to statutory regulations. The data used in this research is secondary data. Then the data was analyzed qualitatively and presented in descriptive form.